STUDY OF THE CAUSES OF ROAD DAMAGE TO CAPTAIN HARUN TOHIR STREET, GRESIK EAST JAVA - Ramadhani, Ardhi; Muhammadun, Haris; Oetomo, Wateno (Transpublika Publisher, 2022)
This study aims to make a study and technical planning of the road following the traffic of heavy vehicle loads through the Harun Tohir road. Road maintenance is an activity to maintain, repair, add or replace existing physical buildings so that their functions can be maintained or enhanced for a longer period. This maintenance guideline is intended to regulate the procedures for carrying out rigid pavement maintenance activities, and maintain stable serviceability conditions, to provide safety and comfort to road users. This guideline for the maintenance of rigid pavements includes descriptions of the types of damage that commonly occur in rigid pavements, their possible causes, follow-up consequences, recommendations for handling, and methods.